A SIMPLE EXPERIMENTAL EQUIPMENT FOR DETERMINING THE INITIAL SPEED OF PROJECTILE MOTION BASED ON COMBINATION OF FREE-FALL AND PROJECTILE MOTION - DIAN RAHMAWATI (NIM: 20207093), MURNI
A simple experimental equipment for determining the initial speed of projectile motion based on combination of free-fall and projectile motion has been made. The equipment is set so the free-fall object can be colliding with the projectile object at some positions. The initial speed of the projectile object can be determined from the length of the path of free-fall object. The initial speed of the projectile object also has been analyzed by dynamical analysis using conservation of mechanical energy and momentum of the projectile launcher.